Analisis SWOT Pemasaran Cabai pada Koperasi Primadona Situbondo - Mayangsari, Andina; Wijaya, Rifky Agnitian; Mufid, Ahmad (Universitas Galuh, 2024)
This research aims to find out what marketing strategies are used by the Primadona Cooperative. The informants in this research were 30 people consisting of chairman, deputy, secretary, staff, members and consumers of the prima donna cooperative. The formulation of alternative strategies was analyzed by creating an Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrix, then continued with a grand strategy and SWOT analysis. SWOT analysis is an analysis used to evaluate the strengths and weaknesses in the internal environment as well as the opportunities and threats in the company's external environment. From the results of the analysis, it was concluded that the competitive position of red chili agribusiness is in quadrant I (high market growth and strong competitive position).